Depression restoration in university students: Data-driven insights across three types of campus greennessOSF - Chaoyi Cui; Qianchen He; Huiming Liu (Data in Brief)
This data examines the relationship between campus green spaces and university students’ mental health, focusing on their restorative potential and the factors influencing engagement. Using a dataset of 818 participants, the data examines three distinct university campus types in Macau with different levels of campus greenness: (1) City University of Macau, a compact, high-density campus with rooftop gardens and small landscaped areas; (2) Macau University of Science and Technology, a medium-density campus with fragmented green space and shaded pathways; and (3) University of Macau, a low-density campus with large gardens, tree-lined pathways, and access to natural landscapes. Exploratory and confirmatory factor analyses validated the measurement model, confirming the reliability and theoretical coherence of constructs such as Perceived Greenness, Perceived Restoration, and Self-Rating Depression. The data allow for a robust investigation into how different campus spatial configurations and green space attributes—such as accessibility, quality, and visual appeal—relate to student mental well-being. The dataset offers meaningful value to researchers and practitioners in urban planning, environmental design, landscape architecture, and educational studies.